An incomplete education 3,684 things you should have learned but probably didn't - Jones, Judy 1946-; Wilson, William 1948-. (New York Ballantine Books, 2006)
A survey of world culture covers American studies, art history, economics, film, literature, music, philosophy, political science, psychology, religion, science, and world history.
American studies -- Art history -- Economics -- Film -- Literature -- Music -- Philosophy -- Political science -- Psychology -- Religion -- Science -- World History -- Lexicon.
Keywords: Handbooks, vade-mecums, etc